Analisis Klorin Pada Pembalut Secara Spektrofotometri UV-Vis, dan Titrasi Iodometri (Literatur Review) - Azizah Nurma Qurotul ‘Aini; Farah Aulia Qatrunnada A; Nabila N; Firdha Senja Maelaningsih (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Sanitary napkins are medical devices used to absorb menstrual blood. Sanitary napkins are usually made from cotton, rayon, a mixture of rayon and cotton. Sanitary napkins are products that use chlorine as one of the ingredients and function as a preservative. Chlorine is a chemical commonly used to kill bacteria. Chlorine reacts with water to form hypochlorous acid. This substance is known to damage cells in the body. The aim of this research is to analyze the concentration of chlorine in women's sanitary napkins. This research uses a literature review research method by collecting data from various sources taken from several research articles from Google Scholar. There were 4 journals used in this research. Based on the results of the literature review that was carried out, it was found that most sanitary napkins had unsafe chlorine concentrations on average of 4.716 mg/g, 0.032 mg/g, and 0.37 mg/g. However, there are sanitary napkins whose safe chlorine concentration is 0.0025 mg/g. In accordance with the requirements of Minister of Health Regulation Number 492/Menkes/Per/IV/2010 concerning the limit for chlorine contained in drinking water of 5 mg/l or 5 ppm and changed to 0.00625 mg/gram.